2007
DOI: 10.1074/mcp.m700056-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Virus-derived Platforms for Visualizing Protein Associations inside Cells

Abstract: Protein-protein associations are vital to cellular functions. Here we describe a helpful new method to demonstrate protein-protein associations inside cells based on the capacity of orthoreovirus protein NS to form large cytoplasmic inclusions, easily visualized by light microscopy, and to recruit other proteins to these structures in a specific manner. We introduce this technology by the identification of a sixth orthoreovirus protein, RNA-dependent RNA polymerase 3, that was recruited to the structures throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…pCI-NS(14-721), pCI-NS(41-721), pCI-NS(173-721), pCI-NS(221-721), and pCI-NS(471-721) were described previously but were originally named pCI-M3(14-721), pCI-M3(41-721), pCI-M3(173-721), pCI-M3(221-721), and pCI-M3(471-721), respectively (5,8,33). pCI-3/HA expressing a C-terminally HA-tagged version of 3 was described previously (32). pEGFP/NS(471-721) was described previously but was originally named pEGFP-C1-M3(471-721) (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…pCI-NS(14-721), pCI-NS(41-721), pCI-NS(173-721), pCI-NS(221-721), and pCI-NS(471-721) were described previously but were originally named pCI-M3(14-721), pCI-M3(41-721), pCI-M3(173-721), pCI-M3(221-721), and pCI-M3(471-721), respectively (5,8,33). pCI-3/HA expressing a C-terminally HA-tagged version of 3 was described previously (32). pEGFP/NS(471-721) was described previously but was originally named pEGFP-C1-M3(471-721) (5).…”
Section: Methodsmentioning
confidence: 99%
“…We previously developed an assay that exploits the characteristic ability of NS, as well as the rotavirus protein NSP5 fused at its amino terminus (N terminus) to enhanced green fluorescent protein (EGFP) (34), to form distinctive structures in the cytoplasm in order to identify and map protein-protein interactions (32). In the current study, we modified and made extensive use of this novel assay to explore further the associations between NS and other MRV proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inactive mutant Figure 6A). In COS-7 cells, which expressed large T antigen known to inhibit the growth-regulatory function of pRB (Gluzman, 1981;Chellappan et al, 1992;Miller et al, 2007), the ARF1 mutant was not found in the nucleus but perinuclearly (Supplementary Figure 6B). To further determine whether the endogenous expression of pRB could regulate the enrichment of endogenous ARF1 or ARF1T 31 N in chromatin, we next overexpressed E7 to specifically decrease pRB level.…”
Section: Arf1 Controls Cell Proliferation P-l Boulay Et Almentioning
confidence: 99%
“…When expressed in transfected cells from a plasmid, NS forms inclusions similar to VFs that are termed viral factory-like (VFL) structures (9). Moreover, NS formation of VFLs results in specific VFL localization of each of the five viral structural proteins that make up the core particle ( 1, 2, 3, 2, and 2), the nonstructural NS protein that is involved in virus translation and replication, as well as the intact core particle itself (6,(9)(10)(11). The mechanism of VFL formation by NS is not fully understood; however, several regions of the protein, including the carboxyl (C)-terminal 7 amino acids (aa) and a putative metal chelating structure formed by amino acids His570 and Cys572, have been shown to be necessary for VFL formation in transfected cells and replication in infected cells (12)(13)(14).…”
mentioning
confidence: 99%